2018
DOI: 10.1021/acs.inorgchem.7b03221
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Molecules in the New Spinel GaV2O4

Abstract: The structures and properties of vanadium oxides are often related to the formation of molecule-like clusters of vanadium cations through direct V-V bonding. GaVO, a new vanadium spinel, was synthesized. Powder diffraction and X-ray total scattering studies, complemented by magnetization and resistivity measurements, reveal that the low-temperature phase of this material is structurally distorted and features ordered pairs of three- and four-atom vanadium clusters. These clusters persist into a disordered cubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Although the timescale for these structural fluctuations is not directly measured, their lack of correlation with phonon motions suggests that they are essentially static or slowly diffusing. A recent quasi-elastic neutron scattering study of GaV 2 O 4 spinel above the 415-K charge-ordering transition found that structurally disordered orbital molecules remain well defined and without measurable dynamics up to 1100 K 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the timescale for these structural fluctuations is not directly measured, their lack of correlation with phonon motions suggests that they are essentially static or slowly diffusing. A recent quasi-elastic neutron scattering study of GaV 2 O 4 spinel above the 415-K charge-ordering transition found that structurally disordered orbital molecules remain well defined and without measurable dynamics up to 1100 K 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the interatomic pair distribution function (PDF) 11 derived from total X-ray scattering data is a simple method for exploring local structure that is highly sensitive to the displacements of metal atoms associated with the formation of orbital molecules, metal–metal-bonded clusters such as the trimerons observed in magnetite 12 . Persistence of orbital molecules far above their long-range electronic ordering transitions has been discovered from X-ray PDF studies of Li 2 RhO 4 13 , Li 2 RuO 3 14 , AlV 2 O 4 15 , and GaV 2 O 4 16 .…”
Section: Introductionmentioning
confidence: 99%
“…17+ heptamers) are found [8,9]. The isoelectronic material GaV 2 O 4 behaves similarly [10]. The orbital molecules in the R3m structures of these materials are defined by short V-V distances, and an EXAFS study of LiV 2 O 4 identified similar shortening above 12 GPa at 300 K [11].…”
Section: Introductionmentioning
confidence: 83%
“…The Fe 2+ sites within the Fe 2+ /Fe 3+ charge-ordered array show a combination of orbital ordering and bonding to two Fe neighbours to form linear three-atom trimeron units, spin-polarised orbital molecules 10 . Orbital molecules associated with charge ordering have also been reported in other materials, such as CuIr 2 S 4 11 , AlV 2 O 4 12,13 , GaV 2 O 4 14 and CaFe 3 O 5 15 . Complex charge orders may lead to spontaneous formation of structurally inequivalent cations of the same charge, for example, ordering of V 4+ /V 5+ over eight inequivalent sites in α′-NaV 2 O 5 16 , and notably in the Cc magnetite superstructure where charges are localised over sixteen distinct octahedrally coordinated sites, eight for Fe 2+ and eight for Fe 3+ .…”
mentioning
confidence: 64%